Genótipos cagA, vacA e alelos de H. pylori em pacientes portadores de gastrite, úlcera péptica e câncer gástrico - Cavalcante, Meyssa Quezado de Figueiredo (2010)
The bacterial species H. pylori is closely correlated with the development of major diseases and gastric cancer of the stomach. The strains that have more pathogenic genotype are more involved in bacterial virulence. The objective was to genotype strains of H. pylori from patients with gastritis, gastroduodenal ulcer and gastric cancer as the cagA and vacA genes and alleles by PCR technique. The genotyping of strains of H. pylori was performed by PCR technique. We evaluated 134 strains, 76 of patients with gastritis, 28 peptic ulcer and 30 gastric cancer. As a result of this research it was found that all strains subtyped were vacA positive, and 48.5% with the allele s1m1 vacA, vacA s1m2 20.9% and 6.7% s2m1 vacA, vacA s2m2 8.2%; 7 5% were hybrid strains and 8.2% had only the allele of the sequence signal (s). Gastritis in the distribution of vacA alleles were: 46.1% s1m1, s1m2 22.4%, 5.3% s2m1, s2m2 11.8%, 3.9% and 10.5% hybrid strains only with allele s. In cases of ulcer was found: 50% s1m1, s1m2 21.4%, 17.8% s2m1, s2m2 3.6%, 7.2% hybrid strains. In patients with cancer met: s1m1 53.3%, 16.7% s1m2, s2m2 3.3%, 16.7% and 10.0% hybrid strains with allele only s. The cagA gene was observed in 82.8% of strains, where 73.7% had gastritis and cagA positive, 96.4% had peptic ulcer and gastric cancer harbored 96.7% were positive for this gene. Allele vacAs1m1 was the most prevalent observed in the three groups. We have also found strains with multiple alleles of this gene, suggesting a genetic polymorphism arising from infection by more than one type of strain in the same individual. The cagA gene was also highly prevalent in both groups. The presence of cagA was statistically significant in the group of pangastritis and gastric cancer. The relationship of the cagA gene with allele vacAs1m1 was also significant in the groups of pangastritis and gastric cancer, which supports the higher pathogenicity of strains of the studied individuals.